Study of Antocyanins Activity from Purple Sweet Potato for Reducing Apoptotic Cells Expression of The Cerebellum On Ischemic Stroke Rats - Latifah Tribuana Dewi; Made Oka Adnyana; Chanif Mahdi; Sasangka Prasetyawan; Arie Srihardyastutie; Aulanni’am Aulanni’am (The Journal of Pure and Applied Chemistry Research, 2018)
This study aims to determine anthocyanin antioxidant performance with a dose of 2 cc/day based on the expression of apoptotic cells on ischemic stroke rats cerebellum. Research was conducted using ischemic stroke rats (Rattus norvegicus) that prepared by ligated for 3 h on the Common Carotid Artery (CCA) and External Carotid Artery (ECA) followed by reperfusion that commonly known as MCAO (Middle Cerebral Artery Occlusion). The anthocyanin extract was characterized by LC-MS and its IC50 was measured by DPPH method. The rats were divided into five groups 1) negative control; 2) reperfusion 1 h; 3) reperfusion 72 h; 4) reperfusion 24 h, with anthocyanin therapy; 5) reperfusion 72 h, with anthocyanin therapy. The results of LC-MS showed that anthocyanin from purple sweet potato extracts contained Petunidin-3,5-O-diglucoside (Pt-DG) with an IC50 value of 22.16 μg/mL, categorized as very strong antioxidant. The results showed that apoptotic cells expression of cerebellum decreased significantly (p<0.01) after 72 h reperfusion with anthocyanins therapy until 2.42%. The current work proved that anthocyanin extract effectively suppresses the apoptotic cell’s expression of the cerebellum on stroke ischemic rats.